2017
DOI: 10.18632/genesandcancer.161
|View full text |Cite
|
Sign up to set email alerts
|

The induction of endoreduplication and polyploidy by elevated expression of 14-3-3γ

Abstract: Several studies have demonstrated that specific 14-3-3 isoforms are frequently elevated in cancer and that these proteins play a role in human tumorigenesis. 14-3-3γ, an isoform recently demonstrated to function as an oncoprotein, is overexpressed in a variety of human cancers; however, its role in promoting tumorigenesis remains unclear. We previously reported that overexpression of 14-3-3γ caused the appearance of polyploid cells, a phenotype demonstrated to have profound tumor promoting properties. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…4 c). Collectively, the expression of H2B-GFP combined with the quantification of DNA content—as outlined in this protocol—enables DNA ploidy to be correlated with several cellular parameters, and was recently employed to examine the length of mitosis and to enumerate the frequency of mitotic errors in polyploid cells induced by overexpression of YWHAG [ 11 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 c). Collectively, the expression of H2B-GFP combined with the quantification of DNA content—as outlined in this protocol—enables DNA ploidy to be correlated with several cellular parameters, and was recently employed to examine the length of mitosis and to enumerate the frequency of mitotic errors in polyploid cells induced by overexpression of YWHAG [ 11 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Our method of measuring DNA content at the end of a time-lapse experiment was recently performed to study polyploid cells as they progressed through cell division [ 11 ]. We reasoned that polyploid cells could be identified using our method, as DNA content and DNA ploidy are interdependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Sharma et al determined that the mTOR signaling pathway, a known regulator of cell metabolism, plays an important role in the polyploidy state in cancer cells. Moreover, Other studies have also shown the importance of HIPPO, 14-3-3 and Hypoxia signaling pathways in the induction of polyploidy in tumor cells [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…One of the potential sources of stem cells is polyploid cells characterized by multinucleation and cell cycle arrest [ 10 , 11 ]. Polyploidy was shown as an adaptation mechanism that allows cancers to tolerate harsh treatment conditions and plays significant role in the drug-resistance of many cancers and cancer cell lines, including NSCLC [ 12 , 13 ]. The polyploid giant cancer cells (PGCCs) could reversibly enter the therapy-induced senescence, allowing them to survive therapy and later re-enter the cell cycle to form daughter cells of typical size and ploidy [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%